A novel calcium-binding peptide from bovine bone collagen hydrolysate and chelation mechanism and calcium absorption activity of peptide-calcium chelate. (1st June 2023) - Qi, Liwei; Zhang, Hongru; Guo, Yujie; Zhang, Chunhui; Xu, Yang
Graphical abstract: Highlights: A novel calcium-binding peptide was screened based on CaSR. The possible chelating mechanism of EYG-Ca was investigated. The stability of EYG-Ca at different conditions was explored. The calcium absorption activity of EYG-Ca was verified. Abstract: A novel calcium-binding peptide from bovine bone collagen hydrolysate was screened based on a new target—the calcium-sensing receptor (CaSR), and its chelation mechanism and calcium absorption activity were investigated. Glu-Tyr-Gly exhibited superior binding affinities to CaSR because of its interaction with the active sites of the CaSR Venus Flytrap (VFT) domain. Glu-Tyr-Gly-Ca may exist in five potential chelation modes and its potential chelation mechanism was that calcium ions were located in the center and surrounded by ionic bonds (carboxyl group) and coordination bonds (carbonyl, amino, and carboxyl group). Glu-Tyr-Gly-Ca was slightly damaged in the intestinal fluid and at different temperatures, whereas it was severely damaged in the gastric fluid and acidic conditions. The results of the calcium dialysis percentage and Caco-2 cells experiments showed that Glu-Tyr-Gly-Ca possessed good calcium transport activity and bioavailability. The findings provided theoretical basis for Glu-Tyr-Gly-Ca as potential calcium supplement to improve intestinal calcium absorption.